Serum uric acid levels during pregnancy: a predictive marker for hypertensive disorders in antenatal women - Sankhe, Darshan; Kose, Varsha D.; Bhalerao, Anuja (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Hypertensive disorders of pregnancy i.e., gestational hypertension, preeclampsia and eclampsia, are most common medical disorders of pregnancy and have serious implications on feto-maternal health outcomes. Owing to substantial risk to both mother and baby, one of emerging area of interest is the role of serum uric acid levels as a potential predictor of hypertensive disorders during pregnancy, notably preeclampsia. This comprehensive review focuses on role of serum uric acid levels, as a prescient marker for hypertensive complications in pregnant women. The review included the original research articles studying role of serum uric acid early detection of hypertensive disorders of pregnancy in pregnant women with gestational age >20 weeks. Original articles having primary data of study of predictive markers of hypertensive disorders of pregnancy were reviewed thoroughly for their demographic indicators, serum uric acid level and feto-maternal outcome of pregnancy. All the studies showed a significant high serum uric acid level among pre-eclamptic women compared to normotensive or pregnant women with gestational hypertension. The ROC also showed greater sensitivity and specificity compared to other markers such as serum calcium and serum creatinine. To conclude, this comprehensive review underscores the pivotal role of serum uric acid levels in predicting adverse maternal and fetal outcomes during pregnancy. This valuable insight has the potential to significantly enhance the care and outcomes for pregnant women and their unborn children facing hypertensive disorders.